MicroRNA-1-3p Suppresses Malignant Phenotypes of Ameloblastoma Through Down-Regulating Lysosomal Associated Membrane Protein 2-Mediated Autophagy - Niu, Xing; Huang, Biying; Qiao, Xue; Liu, Jinwen; Chen, Lijie; Zhong, Ming (Frontiers in Medicine, 2021)
Objective: Several clinical trials have suggested that autophagy inhibition is a promising approach for cancer therapy. However, the implications of autophagy in ameloblastoma (AB) remain undiscovered. This study investigated the dysregulated autophagy and its regulatory mechanisms in AB. Methods: The expression and distribution of autophagy-related proteins including B-cell lymphoma-2-interacting protein-1 (Beclin1), microtubule-associated protein 1 light chain 3 (LC3) II/I and lysosomal associated membrane protein 2 (LAMP2) were detected in AB and normal oral mucosa (NOM) tissues by immunohistochemistry and western blot analyses. Under transmission electron microscopy, the autophagy of AB was observed. LAMP2 was a potential target mRNA of miR-1-3p. Quantitative Real-time PCR (qRT-PCR) analysis was utilized for examining LAMP2 and miR-1-3p in AB tissues as well as AM-1 cells. The correlation between LAMP2 and miR-1-3p was analyzed in AB. After transfection with miR-1-3p mimic or inhibitor, LAMP2 expression, proliferation, migration, and invasion were separately detected in AM-1 cells. Rescue assays were finally presented. Results: Our results showed that Beclin1 was lowly expressed as well as LC3II/I and LAMP2 were highly expressed in AB. Autophagosomes were observed in AB. MiR-1-3p was lowly expressed in AB, which exhibited negative correlations to LAMP2 expression. MiR-1-3p up-regulation significantly lowered LAMP2 expression in AM-1 cells. Furthermore, miR-1-3p overexpression restrained proliferative, migrated, and invasive capacities of AM-1 cells, which were ameliorated by LAMP2 overexpression. Conclusion: Our findings demonstrated that miR-1-3p suppressed malignant phenotypes of AB through down-regulating LAMP2-mediated autophagy, which could become an underlying target for AB therapy.